Pengaruh kualitas produk, harga dan promosi terhadap keputusan pembelian shampo Pantene - Wulandari, Della Umi; Sukaris, Sukaris (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The impact of three primary factors—product quality, price, and promotion—on consumers' decisions to buy Pantene shampoo is the major emphasis of this study topic. Data indicates a fall in the top brand ranking of shampoo brands in recent years, despite Pantene's ability to hold onto its market share. This drop is indicative of the highly competitive nature of the shampoo industry. The purpose of this study is to ascertain how much customer purchase decisions are influenced by Pantene product quality, price, and promotions. It also aims to offer more insight into consumer preferences for shampoo selection and adapt to changes in an increasingly sophisticated market. Using an Accidental Non Probability Sampling approach, 110 Muhammadiyah Gresik students who had bought Pantene shampoo products made up the research sample. This study used multiple linear regression analysis as its analytical method. The study's findings indicate that consumer decisions are significantly influenced by the Pantene shampoo products' price, quality, and marketing.